Measurements and model calculations of HCl column amounts and related parameters over McMurdo during the austral spring in 1989 - Liu, X.; Blatherwick, R. D.; Murcray, F. J.; Keys, J. G.; Solomon, S. (1992)
Solar spectra obtained from a ground-based Fourier transform infrared instrument at McMurdo (Antarctica) in the spring of 1989 have been analyzed to determine total HCl column amounts. A one-dimensional photochemical model was used to simulate the rate of recovery of HCl in the springtime. Low column amounts (about 1 x 10 exp 15 molecules/sq cm) were observed in early September and may be attributed to the heterogeneous conversion of HCl to active chlorine species during the polar night. The rate of recovery of HCl is consistent with its production by chlorine atoms reacting with methane and is dependent on concentrations of active chlorine species and NO molecules in the altitude region from 12 to 22 km. High HCl column amounts (about 7 x 10 exp 15 molecules/sq cm) were observed following recovery in late October, suggesting that the lower stratosphere in the polar region had descended relative to mid-latitudes and that the degree of dechlorination of the transported air was very small.